Hubungan Antara Faktor Risiko Hendaya Kognitif Ringan Pada Pasien Lanjut Usia Di Jakarta Timur - Erlina Erlina Pudyastuti; Zamrina Adilafatma (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2023)
The research objectives in detail are to determine the risk factors for mild cognitive impairment in the elderly and understanding the factors that affect the majority of mild cognitive impairment in the elderly. This research is an observational case-control study and the research method used is multi-variant data analysis and epidemiological information. The results between methods describe the effect of hypertension and physical activity have big influence on mild cognitive. Conclusion The factors that most influence mild cognitive impairment are hypertension and physical activity